PRODUCTION ACTIVITIES IN ISLAMIC ECONOMICS FROM AL-GHAZALI’S PERSPECTIVE - Nuur Rasyidah, Alvi; Mugiyati, Mugiyati (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
This research aims to describe the production activities according to AlGhazali. He explained that Al-Ghazali's economic thought can be divided into four main categories, namely the concept of voluntarism and market evolution, production activities, the barter system and the development of money, as well as the role of the state in public financial management. Using a qualitative research method based on literature study, this research analyzes various major literatures such as the book of Ihya Ulumuddin. The results show that in Al-Ghazali's view, production activities must be carried out in stages, involving coordination and cooperation in order to run effectively and efficiently. Production in Islam is not only oriented towards material profit, but also must pay attention to sharia principles, such as justice, honesty, and community welfare. Al-Ghazali divided production into several main sectors, including agriculture, industry and services, and emphasized the importance of managing factors of production such as land, labor, capital, technology and management. Healthy competition is allowed to encourage innovation by avoiding usury, fraud and injustice, and the principles of sharia for the welfare of society and the pleasure of Allah